Impact of pictorial warnings on tobacco packs in India - Ramesh Nagarajappa1, Debasruti Naik2, Gayathri Ramesh3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Tobacco use is represented as the most important public health predicament as well as the number onereason of preventable death worldwide. India ranks the largest tobacco producer as well as the secondbiggest exporter of tobacco commodities globally. Numerous people each year are killed because of tobaccoconsumption as it affects every organ and system of the body. Hence policies need to be directed towardstobacco control globally. This review article highlights the impact of one such policy - pictorial messageson tobacco warnings.